Evaluasi Kesesuaian Penerimaan dan Penyimpanan Obat di Apotek Syafaka Kudus Berdasarkan Standar Pelayanan Kefarmasian - Muhammad Binsar Dhiya Ulhaq; Zaenal Fanani; Ahmad Suriyadi Muslim (Universitas Respati Indonesia, 2026)
Pharmaceutical services in pharmacies aim to ensure the quality, safety, and effectiveness of medicines received and dispensed to patients. The processes of drug receiving and storage are essential components of drug management that must be carried out in accordance with the Technical Guidelines for Pharmaceutical Service Standards in Pharmacies. Non-compliance with these processes may affect drug quality and the overall quality of pharmaceutical services. This study aimed to evaluate the compliance of drug receiving and storage processes at Syafaka Pharmacy, Kudus, based on the Technical Guidelines for Pharmaceutical Service Standards in Pharmacies. This study employed a descriptive quantitative design with a cross-sectional approach. Data were collected through direct observation using an observation checklist developed based on pharmaceutical service standard indicators, supported by interviews and documentation. Data were analyzed descriptively by calculating the percentage of compliance and categorizing the results based on predetermined criteria. The results showed that the compliance level of the drug receiving process was 87.5%, categorized as highly compliant, while the compliance level of the drug storage process was 82.35%, also categorized as highly compliant. In conclusion, the drug receiving and storage processes at Syafaka Pharmacy, Kudus, were generally compliant with the Technical Guidelines for Pharmaceutical Service Standards in Pharmacies. However, improvements in administrative procedures and storage facilities are necessary to further enhance the quality of pharmaceutical services.